Transformation of RRI Bengkulu Public Relations in Strengthening Audience Relations in the Media Convergence Era - Raypaldo Agustian; Martha Heriniazwi Dianthi; Dilmai Putra (Journal of Law, Social Science, and Management Review, 2026)
PeThis study examines the transformation of Public Relations at RRI Bengkulu in strengthening audience relations in the era of media convergence. The research is motivated by the shift of public broadcasting communication from one-way dissemination to a more dialogic, interactive, and participatory digital model, particularly through Instagram. This study employed a descriptive qualitative approach using in-depth interviews, observation, and documentation. The findings reveal three main strategies: multimedia strategy through vertical videos, images, audio, and text; multichannel strategy through radio, Instagram, TikTok, Facebook, YouTube, official website, and off-air activities; and multiplatform strategy to expand audience reach and participation. These strategies make RRI Bengkulu public relations more adaptive, responsive, and audience-oriented